Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.6060/mhc2009.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Tetrahetarenoporphyrazines

Abstract: Authors review their works on elaboration of new synthetic approaches to heterocyclic analogues of phthalocyanine -porphyrazines with fused fragments of pyridine, pyrazine, quinoline, quinoxaline, tetraazanaphthalene, tetraazaantracene, thiophene and benzothiophene, and (1950-2008) in 1973-1976

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…This methodology is based on a study of cyclization of azido-group with 1,3-diketones, described in reference [28] . It was established that the maximum yields (58-64 %) of the target 4-acetyl-5-methyl- [1,2,3]triazol-1-yl-5-styrylphthalonitriles (9a-c) could be achieved by stirring the starting substrates 8a-c with acetylacetone in the presence of triethylamine in dioxane at 75-85 °C (Scheme 5). At lower temperatures the reaction is slow and not fully completed, and carrying out synthesis at a higher temperature is associated with a significant increase in the amount of reaction byproducts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This methodology is based on a study of cyclization of azido-group with 1,3-diketones, described in reference [28] . It was established that the maximum yields (58-64 %) of the target 4-acetyl-5-methyl- [1,2,3]triazol-1-yl-5-styrylphthalonitriles (9a-c) could be achieved by stirring the starting substrates 8a-c with acetylacetone in the presence of triethylamine in dioxane at 75-85 °C (Scheme 5). At lower temperatures the reaction is slow and not fully completed, and carrying out synthesis at a higher temperature is associated with a significant increase in the amount of reaction byproducts.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds are the most commonly used precursors for the preparation of various macroheterocyclic systems including tetrahetarenoporphyrazines, [1] porphyrinoids, [2] triazaporphyrins, [3] crown phthalocyanines, [4,5] azaphthalocyanines, [6] carborane substituted phthalocyanines, [7] phthalocyanine-fullerene conjugates, [8] binuclear phthalocyanines, [9] and a number of other metalfree phthalocyanines and their metal complexes. [10][11][12][13] Although they have unique chemical and thermal stabilities, phthalocyanines are practically insoluble in water and most organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…TPyzPzs bearing different aromatic heterocycles (pyrazine [11,250,268,269], pyrrole [106], indole [270,271], triazole [272], thianaphthene [273,274] and phenanthroline [275][276][277][278][279]) or dibenzo[b,f]azepine [280] fused to pyrazine rings were reported or mentioned in the literature ( [268,269] or their synthesis was announced [11], but no details on their characterization and properties were provided. Only two reports in a peer-review journals can be found with full characterization of the macrocycle [TPyz159cPzM] bearing eight 4-tert-butylphenyl substituents [250] and [TPyz165bPzM] with eight tert-butylsulfanyl substituents [251].…”
Section: Tpyzpzs With Annulated Heteroaromaticsmentioning
confidence: 99%
“…Linstead first briefly reported on TPyzPzs in his pioneering work in 1937 [1]. However, their systematic study started only in the late 1960s (mainly in the former Soviet Union by Lukyanets [2][3][4][5] and Korzhenevskii [6][7][8][9][10][11][12] and became really active over the last two decades. Among the over 300 papers and patents on the synthesis, properties and applications of this class of porphyrazines which can be currently found by SciFinder ® , about 90% have appeared after 1990 and more than 100 in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] При этом достигается модифицирование каждой молекулы MPc необходимым числом функци-ональных фрагментов. Поверхность частиц MPc также может быть модифицирована посредством гетерофазных реакций с органическими молекулами.…”
Section: Introductionunclassified